Dever estatal de promoção de políticas públicas sobre energias renováveis : limites e desafios na criação de uma política nacional com base no direito comparado e compromissos internacionais assumidos - Sartori, Paola Mondardo (2023)
From the moment the consequences caused by the excessive use of natural resources and the excessive consumption of our time became visible, a new environmental awareness was established in the world, focused on the implementation of a sustainable development. In line with other international legal systems, it was established in art. 225 of the Brazilian Constitution the right of all to an ecologically balanced environment, imposing on the Government and the community the duty to defend and preserve it for present and future generations. Power generation is one of the main topics when talking about environmental protection, considering that its production through non-renewable sources causes immeasurable damage to the planet. The emission of greenhouse gases not only interferes with climate change and the development of fauna and flora but is also responsible for an increasing number of premature deaths and respiratory health issues. Bearing this in mind, in 2015 the Paris Agreement was signed, in which its signatories, including Brazil, committed to reducing greenhouse gas emissions to limit the average increase in global temperature. For the objective to be achieved, more than 90% of the solutions involve renewable energy, either through its direct supply, electrification, energy efficiency or the use of green hydrogen. Aware of this, many countries have included the production of renewable energy within their public policies with a high level of priority and have achieved significant growth in the generation of clean energy in their territories. However, the sector's growth is still slow in Brazil, even though the country has one of the greatest potentials for solar and wind generation in the world. The present study proposes to verify the adequacy or deficiency of the Brazilian state duty of environmental protection in face of the public policies that structure the sector of renewable energies in the national territory by analyzing the international commitments assumed by the country and the comparative law. After the study of Brazilian legislation and the verification of its effectiveness and results, alternative foreign experiences will be sought in case the state's performance is considered deficient. The European Union and, more specifically, Germany were chosen for the study of comparative law, in view of the leading role and wide range of public policies presented both by the economic bloc and by the Germanic country. Through the analysis of its main legislative packages on the subject and the results achieved in its jurisdictions, the possibility of transposing these strategies to the Brazilian reality will be investigated, in order to include them in an eventual National Policy on Renewable Energies that helps in the development of the sector in Brazil. The research is of a theoretical, quantitative and qualitative nature, being classified as explanatory. The procedural methods used were historical, inductive and comparative. The method of interpretation adopted was the systematic one and the study covers a documentary research.